A Study On Antibiotic Utilization Among the Paediatric Inpatients of a Tertiary Care Hospital; A Retrospective Study. - Dr Joychandra Oinam; Dr Neha Thiyam; Dr Laitonjam Jonita Devi; Manjushree Takhellambam (International Journal of Pharma and Bio Sciences, 2022)
The treatment of ailments among paediatric patients with antibiotics significantly affects treating microbial infections but may also produce any type of adverse effects to children. The use of empirical antibiotics may also lead to the development of antibiotic resistance in children1. The study aimed to assess the pattern of antibiotic utilization among the paediatric inpatients. It was a retrospective, observational study for a period of 12 months. The collected data included age, sex, diagnosis, duration of hospital stay, prescribed antibiotics, route of administration, co-administered drugs. Data were entered into a computer, and descriptive statistical analysis was done using SPSS. Bed Head Tickets(BHTs) of 265 inpatients were examined. The common diagnosis were CNS infection i,e 25;21.55%), Respiratory diseases i,e (50;43.10%) and Preterm with Sepsis i,e (14;12.06%) respectively. The maximum number of patients who received antibiotic prescriptions was in the age group between 0 to 1 month i,e (49;42%). The most common antibiotic used was Beta-lactam i,e (86;74.13%) Meropenem (6.66%) followed by Cephalosporin (36.2%), Polypeptides (29.3%), Aminoglycosides (19%) and Macrolides (13.8%). 65(56.03%) of patients received single antibiotics and 49(42.27%) received multiple antibiotics. The average duration of hospital stay was 5.72±4.8 days. The prescription pattern of the antibiotics among the inpatient is not under the aims and objective of the antibiotic stewardship program i,e there is a lot of chance on irrational prescription without microbial investigation like culture and sensitivity. Moreover, the number of case for a period of 12 months is not on the target of tertiary care hospital like Shija Hospital and Research Institute (SHRI). It may be due to the admission or treatment of special and serious cases only.